Analysis of the Role of Social Regulation in the Implementation of Halal Certification to Improve the Competitiveness of MSMEs in Indonesia - Ade Khadijatul Z. Hrp; Rahmat Rahmat (Jurnal Mamangan, 2025)
This study aims to analyze the role of halal certification as a driver of competitiveness for Micro, Small, and Medium Enterprises (MSMEs) in Indonesia, with a focus on the effectiveness of existing regulations. Through a literature review and comparative analysis approach, this study examines the definition, history, and standards of halal certification, as well as its impact on MSME performance and competitiveness. The research methods used include document analysis, in-depth interviews with MSME actors, and a review of government policies related to halal certification. The results show that halal certification has a positive impact on increasing consumer trust, market access, and adding value to MSME products. However, the implementation of halal certification also faces challenges, such as a lack of understanding of the importance of certification, relatively high certification costs, and procedural complexity. Government regulations, including Law Number 33 of 2014 concerning Halal Product Assurance, play a crucial role in facilitating the certification process and boosting MSME competitiveness. The study's conclusion confirms that halal certification is an important catalyst for increasing MSME competitiveness, supported by effective and sustainable regulations. Research implications include recommendations for regulatory improvements, increased awareness of the benefits of halal certification, and provision of technical and financial support for MSMEs